Body fat comparison between basketball and netball players in Malaysia - Soh, Kim Geok; Husain, Ruby; Soh, Kim Lam (Faculty of Medicine, University of Malaya, 2006)
The aim of the study was to compare the body fat percentages between Malaysian national women basketball players and netball players. Both basketball and netball players were elite players who represented Malaysia in the 1997 Southeast Asia Games in Jakarta, Indonesia and the 1998 Commonwealth Games in Kuala Lumpur. The percentage of body fat was determined by means of skinfold measurement at seven different locations. Results of the findings showed that overall, the basketball players had higher percentages of body fat than netball players. The average percentages of body fat of basketball and netball players were 19.68 ± 4.93% and 18.93 ± 4.41%, respectively. Both Malaysian national basketball and netball players' average percentage of body fat were found to be higher than the ideal average percentage of body fat range between 10-16% for female athletes in elite team sports. The players in the defence position in basketball were found to have the highest percentage of body fat (23.00%), followed by centre position players (21.62%) and attack position players (15.10%). These results differed from netball players' in similar playing positions. Among the netball players, the defence position players had the highest percentage of body fat (21.00%), followed by attack position players (18.63%), and centre position players (16.57%).